2014
DOI: 10.5152/jaem.2014.233
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Demographic Properties of the Acute Stroke Patients Admitted to Emergency Department of a Tertiary Referral Center

Abstract: Objective: Stroke is an important cause of morbidity and mortality and has an increasing trend in the emergency department. It has become crucial to treat ischemic stroke with thrombolytic therapy. We reviewed the findings of the initial examinations, arrival times, clinical and demographic characteristics of stroke patients in our emergency department. Material and Methods:One hundred forty-seven stroke patients who registered at the emergency department within the first 24 hours were included in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…38 Previous studies have shown that loss-consciousness is more common in patients with intracerebral hemorrhage compared with ischemic stroke due to increased intracranial pressure and compression of the thalamus and medulla oblongata. 27,33,37,39 There are two symptoms of communication disorders identified in this study, which are aphasia and dysarthria. Aphasia was found more common in subjects with hemorrhagic stroke than ischemic stroke (22.1% vs. 21.6%).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…38 Previous studies have shown that loss-consciousness is more common in patients with intracerebral hemorrhage compared with ischemic stroke due to increased intracranial pressure and compression of the thalamus and medulla oblongata. 27,33,37,39 There are two symptoms of communication disorders identified in this study, which are aphasia and dysarthria. Aphasia was found more common in subjects with hemorrhagic stroke than ischemic stroke (22.1% vs. 21.6%).…”
Section: Discussionmentioning
confidence: 87%
“…26 Percentages in another study showed much greater differences, in which 87.5% of subjects had ischemic stroke and 14.3% subjects had hemorrhagic stroke. 27 Subjects with ischemic stroke were predominantly ≥ 60 years old (56.1%), whereas most subjects with hemorrhagic stroke were < 60 years old (51.4%). The incidence of stroke increased with age.…”
Section: Discussionmentioning
confidence: 98%
“…From 2010 to 2015 there was a 51.4% increase in stroke presentations (Figure 1). Over the five year period, a total of 921 adults made 952 presentations to the ED and were diagnosed with stroke, the majority (n=825, 86.7%) were ischaemic rather than haemorrhagic (n=127, 13.3%) in nature. Of the 952 presentations, a total of 63 were re-presentations with two presentations by 29 patients for ischaemic stroke and one patient for haemorrhagic stroke, while one patient had three presentations of ischaemic stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Stroke is a leading cause of death and disability with an increasing trend of stroke presentations attending the ED. [13] There is limited data on ED stroke presentations in Australia and therefore the aim of this study was to describe stroke presentations to an ED in South-East Queensland Australia. This study found that despite an increase in stroke presentations over the five year period there was a trend towards improvements in most outcomes studied.…”
Section: Discussionmentioning
confidence: 99%
“…Electrolytes play an important role in muscle contraction, electrolytes referred to in this study include sodium, potassium, and calcium 9 . Therefore, researchers want to assess the relationship between serum sodium, potassium, 3 show the relationship of sodium serum levels at admission with MAS scores was tested with the Spearman test.…”
Section: Introductionmentioning
confidence: 99%